2016
DOI: 10.3847/0004-637x/816/2/91
|View full text |Cite
|
Sign up to set email alerts
|

Chromospheric Sunspots in the Millimeter Range as Observed by the Nobeyama Radioheliograph

Abstract: We investigate the upper chromosphere and the transition region of the sunspot umbra using the radio brightness temperature at 34 GHz (corresponding to 8.8-mm observations) as observed by the Nobeyama Radioheliograph (NoRH). Radio free-free emission in the longer millimeter range is generated around the transition region, and its brightness temperature yields the region's temperature and density distribution. We use the NoRH data at 34 GHz by applying the Steer-CLEAN image synthesis. These data and the analysi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…As expected, active regions at mm and sub-mm wavelengths generally appear as bright areas, although sunspot umbrae, if resolved, have lower brightness temperatures than the quiet Sun level at λ ≤ 3.5 mm (Lindsey & Kopp 1995;Loukitcheva et al 2014;Iwai & Shimojo 2015) or have almost equal brightness temperature as the quiet Sun at λ = 8.8 mm (Iwai et al 2016).…”
Section: Introductionsupporting
confidence: 71%
“…As expected, active regions at mm and sub-mm wavelengths generally appear as bright areas, although sunspot umbrae, if resolved, have lower brightness temperatures than the quiet Sun level at λ ≤ 3.5 mm (Lindsey & Kopp 1995;Loukitcheva et al 2014;Iwai & Shimojo 2015) or have almost equal brightness temperature as the quiet Sun at λ = 8.8 mm (Iwai et al 2016).…”
Section: Introductionsupporting
confidence: 71%
“…12) are best suited for comparison with the brightness differences calculated from the models. For completeness, we also plot the observational values obtained from BIMA maps at 3.5 mm by Loukitcheva et al (2014) for the big and small umbrae (triangles), respectively, at a resolution of 12 ; the measurements from JCMT at 0.35, 0.85 and 1.2 mm (diamonds) made by Lindsey & Kopp (1995) at a resolution of 14-17 ; brightness observations at 2.6 and 3.5 mm obtained from the Nobeyama 45-m telescope by Iwai & Shimojo (2015) at a resolution of 15 , and at 8.8 mm from the NoRH by Iwai et al (2016) at a resolution of 5-10 (plus signs). Figure 12 shows that, at wavelengths longer than 1.3 mm, the observed umbral brightness, either averaged over the whole umbra (green circles at 1.3 mm and 3 mm), or measured with moderate spatial resolution (at 2.6, 3.5, and 8.8 mm), is not very different from the QS brightness.…”
Section: Penumbral Modelsmentioning
confidence: 99%
“…In both cases, the umbra was darker than the surrounding atmosphere, albeit with a spatial resolution of [12][13][14][15][16] arcsec that limited their ability to separate typical sunspot umbrae from the surrounding bright penumbra and active region. At a wavelength of 8.8 mm, Iwai et al (2016) found that sunspots are generally not distinguishable from the surrounding atmosphere using the Nobeyama Radioheliograph (NoRH).…”
Section: Introductionmentioning
confidence: 99%